Establishment of the first Chinese national standard for recombinant nuclease used as a process material in pharmaceutical manufacturing - Wang, Lyuyin; Sun, Yue; Xu, Kaixin; Hu, Xinyue; Li, Yi; Lyu, Ping; Liu, Xiao; Li, Jun; Li, Jing (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRecombinant nuclease (RSN) is a critical raw material enzyme essential for removing host nucleic acids during the production of cell and gene therapy products. However, the lack of standardized quality evaluation methods and reference materials for RSN has resulted in poor reliability and comparability of testing results, hindering the standardized development of related industries. This study aimed to establish the first Chinese national standard for RSN activity, thereby enabling accurate and comparable quantification of enzymatic potency across laboratories and industries.MethodsHigh-purity candidate RSN reference materials were prepared and structurally analyzed via mass spectrometry. A robust enzymatic activity assay using herring sperm DNA as the substrate was optimized and validated in accordance with ICH Q2 (R2) guidelines. The assay’s specificity, accuracy, and precision were evaluated, and a collaborative study involving three laboratories was subsequently conducted to determine the potency value.ResultsThe assay exhibited excellent precision (intra-lab coefficient of variation (CV) < 5%, inter-lab CV 2.01%) and accuracy (recovery rate 90–110%). The candidate reference material showed high homogeneity and stability. Collaborative testing confirmed the statistical consistency of the study results (P > 0.05), and the potency of the candidate material was determined to be 518 U/μL.DiscussionThe establishment of this national standard will provide a unified reference for measuring RSN activity, enhance consistency in quality control, and support the safe development and production of biopharmaceuticals (including cell and gene therapies). This standard will serve as a critical tool for regulatory evaluation and industrial applications in China. The optimized content is consistent with the copyedited version of the article, featuring clear logic and comprehensive key information.